Pregnancy and Delivery Outcomes Following Benzodiazepine Exposure: A Systematic Review and Meta-analysis. (December 2020) - Grigoriadis, Sophie; Graves, Lisa; Peer, Miki; Mamisashvili, Lana; Ruthirakuhan, Myuri; Chan, Parco; Hennawy, Mirna; Parikh, Supriya; Vigod, Simone Natalie; Dennis, Cindy-Lee; Steiner, Meir; Brown, Cara; et al.
Objective: Understanding the effects of benzodiazepines (BZDs) on maternal/fetal health remains incomplete despite their frequent use. This article quantifies the effects of antenatal BZD exposure on delivery outcomes. Methods: Data Sources: Medline, PsycINFO, CINAHL, Embase, and the Cochrane Library were searched till June 30, 2018. Study Selection: English-language cohort studies comparing antenatal BZD exposure to an unexposed group on any delivery outcome were eligible. In all, 23, 909 records were screened, 56 studies were assessed, and 14 studies were included. Data Extraction: Two reviewers independently assessed quality and extracted data. Estimates were pooled using random effects meta-analysis. Sub-analyses examined several potential moderators including timing of exposure. Results: There were 9 outcomes with sufficient data for meta-analysis. Antenatal BZD exposure was significantly associated with increased risk of 6 outcomes initially: spontaneous abortion (pooled odds ratio = 1.86; 95% confidence interval [CI], 1.43 to 2.42), preterm birth (1.96; 95% CI, 1.25 to 3.08), low birth weight (2.24; 95% CI, 1.41 to 3.88), low Apgar score (2.19; 95% CI, 1.94 to 2.47), Neonatal Intensive Care Unit (NICU) admission (2.61; 95% CI, 1.64 to 4.14), and induced abortion (2.04; 95% CI, 1.23 to 3.40). There was significant heterogeneity between studies for most outcomes without consistent moderators. Birth weight (mean difference [MD]: −151.35 g; 95% CI, −329.73 to 27.03), gestational age (−0.49 weeks; 95% CI, −1.18 to 0.19), and small for gestational age (SGA; 1.42; 95% CI, 1.00 to 2.01) did not show significant associations although after adjusting for publication bias, gestational age, and SGA became significant, totaling 8 significant outcomes. Conclusions: Antenatal BZD exposure appears to be statistically associated with increased risk of several adverse perinatal outcomes. Although confounds cannot be ruled out, NICU admission does appear clinically relevant and consistent with the antidepressant literature.